Life‐history strategy and behavioral type: risk‐tolerance reflects growth rate and energy allocation in ant colonies. Issue 4 (25th October 2016) - Bengston, Sarah E.; Shin, Min; Dornhaus, Anna
Abstract : Despite the recent interest in animal personality and behavioral syndromes, there is a paucity of explanations for why distinct behavioral traits should evolve to correlate. We investigate whether such correlations across apparently distinct behavioral traits may be explained by variation in life history strategy among individual ant colonies. Life history theory predicts that the way in which individuals allocate energy towards somatic maintenance or reproduction drives several distinct traits in physiology, morphology, and energy use; it also predicts that an individual's willingness to engage in risky behaviors should depend on reproductive strategy. We use Temnothorax ants, which have been shown to exhibit 'personalities' and a syndrome that may reflect risk tolerance at the colony level. We measure colonies' relative investment in growth rate (new workers produced) compared to reproductive effort (males and queens produced). Comparing sterile worker production to reproductive alate production provides a direct measure of how colonies are investing their energy, analogous to investment in growth versus reproduction in a unitary organism. Consistently with this idea, we found that behavioral type of ant colonies was associated with their life history strategy: risk‐tolerant colonies grew faster and invested more in reproduction, whereas risk‐averse colonies had lower growth rate but invested relatively more in workers. This provides evidence that behavioral syndromes can be a consequence of life‐history strategy variation, linking the two fields and supporting the use of an integrative approach.